EFEK SITOTOKSIK FRAKSI ETIL ASETAT EKSTRAK ETANOL UMBI BIT (Beta vulgaris L.var rubra L.) TERHADAP SEL T47D DAN UJI KANDUNGAN KIMIANYA - Sri Susilowati; Iga Dewinta Putri; Aqnes Budiarti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2016)
ABSTRACT Breast cancer is the prime cause of women death in various parts of the world.  Many research  to get breast cancer drug has been widely applied. The aims of    this study were to determine the cytotoxic effect of ethyl acetate fraction of ethanolic extract of the beet root  (Beta vulgaris  L.  var. rubra  L.) on T47D cell line which was the breast  cancer cell and test their chemical compound. The  extract was made by macerare method, and than it was fractionated by using ethyl acetate. Cytotoxicity test using MTT assay method with concentration 500; 250; 125; 62,5; 31,25 µg/ml. Observation was done  to get the viability cell absorbance by using ELISA reader. Analytical data carried out  toward percentage viability T47D cell line  to determine a value IC50.  The chemical compound  tests done through a process of preliminary test with a chemical reagent and thin layer chromatografi. The chemical compound were qualitative analysis. The result showed that ethyl acetate fraction of ethanolic extract beet roots had cytotoxic effect against T47D cell line with IC50 253,86 µg/ml. The chemical compound of the ethyl acetate fraction of ethanolic extract of beet root were flavonoids. Keywords: Ethyl acetate fraction of ethanolic extract of beet roots, Beta vulgaris L. var. rubra L.,  Cell line T47D, Flavonoids